The Effect of Hybrid Learning Method Assisted by Artificial Intelligence Camera Controller and Student Engagement on Learning Outcomes - Agus Fajar Hariadi; I Nyoman Sudana Degeng; Punaji Setyosari; Saida Ulfa; Faiqul Faris Alhakim (Postgraduate, University of Mataram, 2025)
The COVID-19 pandemic disrupted education, causing learning loss due to reduced teacher-student interaction during distance learning. Digital methods often failed to improve engagement and outcomes due to remote monitoring difficulties. A hybrid learning approach integrating offline and online methods was introduced, supported by an Artificial Intelligence Camera Controller (AICC), allowing 50% of students in-person participation while others joined online. This study investigated AICC-supported hybrid learning's impact on student engagement and mathematics outcomes using a quasi-experimental 2x3 factorial design with non-equivalent control groups. The participants of this study consisted of an experimental group of 64 students and a control group of 62 students. Data were collected through observations, questionnaires, and tests, analyzed using Two-Way ANOVA. Results showed AICC-supported hybrid learning significantly improved outcomes compared to hybrid learning without AICC. Findings revealed: (1) no significant difference between high and medium engagement students; (2) no significant difference between medium and low engagement students; (3) significant differences between high and low engagement students. AICC-supported hybrid learning effectively enhances engagement and academic performance, offering a promising post-pandemic educational strategy. Teachers should adopt this method for improved student competencies.